Pengaruh Strategi React Terhadap Penalaran Induktif Matematis Dan Motivasi Belajar Matematika Siswa SMP - Tri Astuti Arigiyati; Agustina Sri Purnami; Rizka Arinil Haq (Universitas Sarjanawiyata Tamansiswa, 2017)
The purpose of this research are to know (1) the influence using REACT learning strategy about increase studentâ€™s mathematical inductive reasoning skills, and (2) the influence using REACT learning strategy about increase studentâ€™s studying motivation. Population of this research was the students grade VIII of SMP. The sample was 34 students as the experimental class that given treatment REACT learning Â and 31student as the control class with expository learning. Data collection in this study by using test and questionnaire techniques. Data were analyzed by using t test. The result of the research showed that 1) the value of sig 0,03 <0,05 meaning that there is influence of applying of REACT learning to improvement of mathematical inductive reasoning ability of student of class VIII SMP, (2) sig value 0,041 <0,05 meaning that there is influence of application of REACT learning to increase motivation learn math class VIII SMP.